Applications of Forensic Accounting in Detecting and Preventing Financial Crimes - Saha, Palash; Dey , Kripa Nath; Chowdhury, Mohammad Shofiqul Islam; Das, Ripon Chandra; khan, Md Miraj Hossen; Tanvir, Md Tasnin; Halimuzzaman, Md. (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
Financial crimes, including fraud, misuse, and money laundering, present considerable risks to Bangladesh's economic stability and public confidence in financial institutions. This paper examines the application of forensic accounting in identifying and mitigating such crimes, evaluating its efficacy, identifying obstacles, and exploring possible legislative measures. A quantitative poll involving 400 respondents from industries such as banking, accounting, auditing, and regulatory organizations indicated that 82% perceived financial crimes as prevalent, whereas 89% asserted that forensic accounting could substantially improve fraud detection. The study revealed multiple obstacles to adoption, including insufficient forensic knowledge (68%), technological constraints (56%), and inadequate regulatory enforcement (63%). Participants endorsed the incorporation of global best practices, including as AI-driven fraud detection and real-time transaction monitoring, while underscoring the necessity for policy reforms, training initiatives, and technical investments to enhance the accessibility and efficacy of forensic accounting. The results suggest that by overcoming these obstacles, Bangladesh can improve its financial crime prevention framework, promote organizational transparency, and establish a more robust financial system.